The Relationship Between Anthropometricity and Physical Condition of The Women’s Kabaddi Team in Central Java - Radhitya Al Ghiffari; Dhias Fajar Widya Permana (Journal of Physical Education Health and Sport, 2025)
Kabaddi is a high-intensity sport that requires speed, agility, strength, and neuromuscular coordination. However, studies on the physiological characteristics and physical condition of kabaddi athletes, especially in Indonesia, are still very limited. This study aims to analyze the anthropometric profile and physical condition of female kabaddi athletes in Central Java and identify the relationship between Body Mass Index (BMI) and physical condition. The study used a quantitative, descriptive approach and involved 12 athletes selected through purposive sampling. The instruments included anthropometric measurements (height, weight, BMI, leg length, and arm span) and physical condition tests (speed, agility, endurance, flexibility, and strength). The data were analyzed using T-Scores and Chi-Square tests. The results showed that the majority of athletes had a BMI in the Obesity I category (58.33%), but most of their physical condition was in the moderate category (41.67%). The Chi-Square test produced a p-value of 0.310, indicating no significant relationship between BMI and physical condition. These findings confirm that BMI is not an accurate indicator of athlete fitness, as athletes with high BMI but excellent physical condition tend to have low body fat and high muscle mass, while athletes with low BMI and poor physical condition have excess body fat that hinders performance. Further research can use more accurate body composition measurements and more specific training programs according to individual needs and playing positions.